Utilization of tiesa (Lucuma Nervosa) in kroepeck - Carandang, Minerva D.; Magluyan, Virginia B. (1979)
A standard formulation for kroepeck using a combination of tiesa and rice flour was developed. The best combination of rice flour, tiesa and hot water (212°F) was found to be 32.5% rice flour, 8.1% tiesa and 59.4% of water as evaluated by a panel of ten members based on color, texture, shape and appearance of the cooked samples. The samples dried to a final moisture content ranging from 5.6% to 6.7% before frying were found to be the crispiest, had the greatest volume expansion and were favored by most of the panelists. Using the same combination but with varying levels of barbecue spice flavoring, panelists were likewise asked to evaluate the color, texture, shape, appearance and flavor of kroepeck samples. An amount of 3.0 g (1.9%) of flavoring per 160.8 g of the dry ingredients gave rise to a pleasant testing snack item. A consumer survey was also held in four different areas to determine the acceptability of the final product. The product was rated by the majority as "like moderately".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruits -- Philippines; Tiesa